Towards forecasting and mitigating ionospheric scintillation effects on GNSS - Aquino, M.; Dodson, A.; DeFranceschi, G.; Alfonsi, L.; Romano, V.; Monico, J. F G [UNESP]; Marques, H. [UNESP]; Mitchell, C. (Institute of Electrical and Electronics Engineers (IEEE), 2007)
The effect of the ionosphere on the signals of Global Navigation Satellite Systems (GNSS), such as the Global Positionig System (GPS) and the proposed European Galileo, is dependent on the ionospheric electron density, given by its Total Electron Content (TEC). Ionospheric time-varying density irregularities may cause scintillations, which are fluctuations in phase and amplitude of the signals. Scintillations occur more often at equatorial and high latitudes. They can degrade navigation and positioning accuracy and may cause loss of signal tracking, disrupting safety-critical applications, such as marine navigation and civil aviation. This paper addresses the results of initial research carried out on two fronts that are relevant to GNSS users if they are to counter ionospheric scintillations, i.e. forecasting and mitigating their effects. On the forecasting front, the dynamics of scintillation occurrence were analysed during the severe ionospheric storm that took place on the evening of 30 October 2003, using data from a network of GPS Ionospheric Scintillation and TEC Monitor (GISTM) receivers set up in Northern Europe. Previous results [1] indicated that GPS scintillations in that region can originate from ionospheric plasma structures from the American sector. In this paper we describe experiments that enabled confirmation of those findings. On the mitigation front we used the variance of the output error of the GPS receiver DLL (Delay Locked Loop) to modify the least squares stochastic model applied by an ordinary receiver to compute position. This error was modelled according to [2], as a function of the S4 amplitude scintillation index measured by the GISTM receivers. An improvement of up to 21% in relative positioning accuracy was achieved with this technnique.
Keywords: Galileo; GNSS; GPS; Ionosphere; Ionospheric scintillation; Total Electron Content (TEC); Atmospheric electricity; Curve fitting; Error analysis; Forecasting; Global positioning system; Ionospheric measurement; Least squares approximations; Light emission; Luminescence; Marine applications; Mathematical models; Navigation; Research; Satellite navigation aids; Stochastic models; Amplitude scintillation index; Delay-locked loop (DLL); Density irregularities; European; Galileo (CO); Global navigation satellite systems (GLONASS); GPS receivers; High Latitudes; In phase (IP); International symposium; Ionospheric electron; Ionospheric plasmas; Ionospheric scintillations; Ionospheric storm; Least squares (LS); Loss of signal; Marine navigation; Mobile multimedia; Monitor (CO); Navigation and positioning; Output error (OE); Paper addresses; Relative positioning; Safety critical applications; Time-varying; Total electron content (TEC); Scintillation